Microbial Inoculants and Fertilizer Reduction in Sorghum Cultivation: Implications for Sustainable Agriculture - Gonçalves, Luana Beatriz [UNESP]; Santos, Carlos Henrique Barbosa [UNESP]; Gonilha, Dalilla Berlanda de Lima [UNESP]; Frezarin, Edvan Teciano [UNESP]; da Costa, Matheus Toller Pires [UNESP]; Rigobelo, Everlon Cid [UNESP] (MDPI, 2025)
Sorghum (Sorghum bicolor L. Moench) is a versatile cereal crop with diverse applications in human food, animal feed, and other industries. This study investigated the effects of microbial inoculation on sorghum growth and nutrient uptake at two fertilizer levels (100% and 80% of the recommended dose). Bacillus subtilis, B. pumilus, B. licheniformis, Purpureocillium lilacinum, and Trichoderma harzianum were applied to the soil and plants in a greenhouse experiment using a completely randomized design with six replicates per treatment. Plant growth parameters, including height, shoot and root dry matter, nitrogen and phosphorus content in the shoots and roots and chlorophyll, were assessed. The results showed no statistically significant differences among the treatments for most parameters, except for plant height and shoot dry matter, where the B. subtilis treatment exhibited the lowest values. Notably, treatments that received 80% of the recommended fertilizer dose performed similarly to those that received 100%, suggesting the potential for reduced fertilizer usage with microbial inoculants. Although the microbial treatments did not significantly enhance sorghum growth in this study, evaluating their effects remains crucial for developing eco-friendly alternatives to reduce chemical fertilizers. Further research is needed to optimize the application of microbial inoculants and to understand their impact on soil health and agricultural productivity under various environmental conditions.